2018
DOI: 10.1183/23120541.00221-2018
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-led cognitive behavioural therapy for treatment of anxiety in COPD

Abstract: Anxiety disorders are common and debilitating conditions that significantly impair the physical functioning and quality of life (QoL) of patients with chronic obstructive pulmonary disease (COPD). A recent systematic review identified the high prevalence of these disorders in patients with COPD, ranging 6–33% for generalised anxiety, 0–44% for panic disorder, 10–27% for specific phobias, and 5–11% for social phobias [1]. Furthermore, under-recognised or untreated anxiety disorders in COPD patients may reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The results obtained showed that the interventions performed by nurses were effective in the short term and long term in reducing the level of anxiety, and/or remission of symptoms and in clinical improvement of symptoms related to comorbidities. This result corroborates previous studies in which reductions in anxiety levels are commonly evaluated together with the reduction of depressive symptoms in interventions performed by nurses (Berg et al, 2020;Pahlavanzadeh et al, 2017;Yohannes, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results obtained showed that the interventions performed by nurses were effective in the short term and long term in reducing the level of anxiety, and/or remission of symptoms and in clinical improvement of symptoms related to comorbidities. This result corroborates previous studies in which reductions in anxiety levels are commonly evaluated together with the reduction of depressive symptoms in interventions performed by nurses (Berg et al, 2020;Pahlavanzadeh et al, 2017;Yohannes, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Richards et al (2003) and Oosterbaan et al (2013) noted in their studies that the CBT can provide cost-related benefits with short-term responses that help reduce public health system expenditures (Izaguirre-Riesgo et al, 2020). In a previous study performed with nurses and chronic respiratory patients, the same economic impact was inferred by reducing emergency visits after individual CBT interventions (Yohannes, 2018).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…There is increasing evidence that integrating mental and physical care for people with long-term conditions can improve both physical and mental health and reduce costs [24]. The question of how to incorporate CBT into routine care has been addressed in a real-world study [8]. My colleagues and I have demonstrated that it is feasible to train respiratory nurses to deliver CBT for patients.…”
Section: Resultsmentioning
confidence: 99%
“…This care model brings significant benefits to patients and cost savings to healthcare services [20]. As Y ohannes [8] has suggested, CBT may be a key step towards improving the care of COPD patients. The challenge facing clinicians, managers and commissioners is to implement this model into routine clinical care and have a clear pathway to refer more complex psychological problems on to mental health teams.…”
Section: Resultsmentioning
confidence: 99%